Community Participation in the Literacy Village Program as an Effort to Improve the Community Literacy Development Index (IPLM) in Cirebon Regency - Muhammad Farhat Luthfi; Siti Khumayah (Salus Publica: Journal of Community Service, 2026)
The Literacy Village Program reflects the local government’s strategic efforts to improve the Community Literacy Development Index (IPLM) particularly by strengthening a community-based literacy culture. In 2024, the IPLM score in Cirebon Regency remains relatively low. Thes condition show that literacy development cannot rely solely on policy-driven approaches but also needs active involvement from the community as the main actors. This study examines how community participation in the Literacy Village Program contributes to improving the IPLM in Cirebon Regency. It applies to a descriptive qualitative approach, with data collected through field observations, in-depth interviews, and documentation. The research subjects include the Cirebon Regency Archives and Library Office, Literacy Village managers, and the local community. The results of the study indicate that community participation in the Literacy Village Program is in the early stages of development. The community is quite actively involved in various literacy activities organized, although involvement in planning and expressing aspirations is still dominated by a small number of individuals. Socially inclusive literacy programs, such as training activities linked to community economic needs, show a positive contribution to increasing community interest and involvement. The findings of this study indicate that community participation is a key factor in the sustainability of the Program.